2017
DOI: 10.3892/or.2017.6077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of miR-7a and miR-24-3p on the SOX18 transcript in lung adenocarcinoma

Abstract: The molecular pathogenesis of the development of non-small cell lung carcinomas (NSCLCs) is extremely complex. Understanding the molecular basis of the development of this malignant tumor may enable the use of targeted therapy, which may result in a better treatment outome for these patients. Adenocarcinoma (AC) is the most common NSCLC subtype, equally common among smokers and non-smokers, and its pathogenesis remains unknown. The SOX18 protein is an important protein that plays a role in the development of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…It has previously been found that miRNA expression is altered in various tumors cells. 11 13 miR-1269 was found to be overexpressed in colorectal, liver and esophagus cancers and to further regulate cell proliferation, apoptosis, epithelial–mesenchymal transition (EMT), and metastasis. 14 17 It is believed that miR-1269 could be a potentially prognostic biomarker and therapeutic target, however the precise role of miR-1269 in lung cancer is as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been found that miRNA expression is altered in various tumors cells. 11 13 miR-1269 was found to be overexpressed in colorectal, liver and esophagus cancers and to further regulate cell proliferation, apoptosis, epithelial–mesenchymal transition (EMT), and metastasis. 14 17 It is believed that miR-1269 could be a potentially prognostic biomarker and therapeutic target, however the precise role of miR-1269 in lung cancer is as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Later experiments revealed the participation of two miRNA molecules in this phenomenon: miR-7a and miR-24-3p (9). The results of the analysis of the level of these molecules in cases of lung adenocarcinoma (AC) and squamous-cell lung carcinoma (SQC) and their corresponding cases of NMLT point to a mechanism carried out by the cancer cells through which they reduce the primary high level of the miRNA molecules found in normal lung tissue (9,52). Therefore, the demonstration of the role of specific miRNAs and the role of the methylation of the SOX18 gene promoter in the above-described mechanism may be used in the future in diagnostics, prognostic assessment and, possibly, in NSCLC targeted therapy as well.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…On the one hand, compared with normal tissues, miR-24 was found to be up-regulated in the following human cancers: lung cancer (LC) ( 6 , 44 , 45 ), hepatocellular carcinoma (HCC) ( 7 ), breast cancer (BC) ( 8 ), tongue squamous cell carcinoma (TSCC) ( 42 ), bladder cancer (BLC) ( 46 ), gastric cancer (GC) ( 47 ), acute leukemia (AL) ( 48 ), and Hodgkin Lymphoma (HL) ( 49 ). On the other hand, miR-24 was found to be down-regulated in the following human cancers: nasopharyngeal carcinoma (NPC) ( 9 ), colorectal cancer (CRC) ( 10 ), laryngeal squamous cell carcinoma (LSCC) ( 11 ), prostate cancer (PC) ( 27 , 28 ), lung adenocarcinoma (LA) ( 29 , 30 ), bladder cancer (BLC) ( 31 ), and gastric cancer (GC) ( 32 ), compared to the normal tissues. Specifically, miR-24 promoted lung cancer progression by regulating the tumor suppressor gene menin ( 45 ).…”
Section: Therapeutic Relevance Of Mir-24 In Cancermentioning
confidence: 99%